2018
DOI: 10.1063/1.5044383
|View full text |Cite
|
Sign up to set email alerts
|

Auger recombination in AlGaN quantum wells for UV light-emitting diodes

Abstract: We show that the often observed efficiency droop in AlGaN quantum well heterostructures is an internal carrier loss process, analogous to the InGaN system. We attribute this loss process to Auger recombination, with C ¼ 2.3 Â 10 À30 cm 6 s À1 ; a similar value found commonly in InGaNbased devices. As a result, the peak internal quantum efficiency (IQE) of our structures is limited to 66%. These values were obtained by resonant excitation (time-resolved) photoluminescence (PL), avoiding common error sources in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 28 publications
2
32
1
Order By: Relevance
“…[28,29] In addition, the room temperature internal quantum efficiency (IQE) of AlGaN epilayers grown by MBE is often evaluated by the temperature-dependent photoluminescence (PL) intensity, [30,31] assuming that the lowtemperature IQE is unity, which is, however, not necessarily a valid assumption. [32] In this article, we follow the track of MBE-grown AlGaN. We first investigate the IQE of AlGaN/AlN double heterostructure (DH) through analyzing the room temperature power dependent PL intensity combining with the Shockley-Read-Hall (SRH) model, which is argued to be sufficient in determining the room temperature IQE.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[28,29] In addition, the room temperature internal quantum efficiency (IQE) of AlGaN epilayers grown by MBE is often evaluated by the temperature-dependent photoluminescence (PL) intensity, [30,31] assuming that the lowtemperature IQE is unity, which is, however, not necessarily a valid assumption. [32] In this article, we follow the track of MBE-grown AlGaN. We first investigate the IQE of AlGaN/AlN double heterostructure (DH) through analyzing the room temperature power dependent PL intensity combining with the Shockley-Read-Hall (SRH) model, which is argued to be sufficient in determining the room temperature IQE.…”
Section: Introductionmentioning
confidence: 99%
“…[ 28,29 ] In addition, the room temperature internal quantum efficiency (IQE) of AlGaN epilayers grown by MBE is often evaluated by the temperature‐dependent photoluminescence (PL) intensity, [ 30,31 ] assuming that the low‐temperature IQE is unity, which is, however, not necessarily a valid assumption. [ 32 ]…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a similar effect was reported and studied in AlGaN‐based epilayers and quantum wells (QWs), which generally suffer from a similar magnitude of TDDs compared with InGaN‐based structures. [ 11–17 ] Despite their continuing inferiority to blue LEDs, research efforts on AlGaN‐based devices emitting in the deep ultraviolet (UV) spectrum have determined IQEs as high as ≈65%, [ 18 ] significantly exceeding the maximum values expected by simple estimations based solely on the influence of the TDDs. [ 19 ] In a recent study, we have shown that the degree of carrier localization in AlGaN/AlN QWs is substantially larger than commonly reported in equivalent InGaN‐based structures and directly affects the IQE and efficiency droop.…”
Section: Introductionmentioning
confidence: 99%
“…believed to work adequately when the excitation is resonant and a "plateau region" of the PL efficiency as a function of excitation power density is observed at low temperatures. 4,6 Time-resolved and timeintegrated CL measurements were performed in an FEI Inspect F50 SEM. A Horiba Jobin Yvon ihR550 spectrometer equipped with a Peltier-cooled charge coupled device detector and a 600 grooves/mm diffraction grating was used for spectral analysis.…”
Section: Sample Structure and Measurement Methodsmentioning
confidence: 99%
“…9 injected into the structures is directly proportional to the applied laser power. According to the ABC model, 4,6 the maximum of the PL efficiency curve is obtained at n=√(A/C), where n is the carrier density,…”
Section: Sample Structure and Measurement Methodsmentioning
confidence: 99%